Factors influencing students' motivation and attitude towards Islamic studies in Lagos state Nigeria - Ayobami, Oseni 'Rahman (Institute of Education, International Islamic University Malaysia, 2012)
This study examines the variable of students' motivation, students' environment and students' attitude towards Islamic studies in Lagos state Nigeria. It equally investigated the relationship between these variables with focus on environmental factors as independent variables against the influence of students' motivation and attitude with a view to understanding how applicable the theory of human development in context can be used to address the suggestive ambivalent attitude of secondary schools' students towards Islamic studies in Lagos state south western Nigeria. Based on the need to get empirical as well as rich data to explore students' perception of what factors influenced their attitude towards Islamic studies, mixed method research design was adopted for this study through questionnaires and interview. The survey comprised of three hundred (300) students in senior secondary schools selected through stratified random sampling. Five students participated in the in-depth interview based on purposeful nested sampling. Factor analysis was conducted to determine the variables that mostly influence students' motivation and attitude, T-Test was conducted to investigate difference in male and female students' attitude, the influence of parents' education and occupation on students' stream of study was examined through ANOVA and Multiple Regression was conducted to find out which factor mostly predict students' attitude towards Islamic studies. The findings of the survey suggest that environmental factors mostly predict students' attitude than students 'motivation, while parents' influence among the micros factors mostly predict students' motivation and attitude. Furthermore, the result of T-test shows that there is no significant difference in male and female students' attitude towards Islamic studies. While the findings of the analysis of the interview data supported the survey results, the qualitative data revealed that difference existed between students based on the type of home and school. The major observation of the study is that the different factors which contribute to students' poor enrolment and academic performance in Islamic studies examination at the Senior Secondary School three can not be divorced from the mutual interaction between students' environment and motivation which appear to be shaping their attitude to the subject. The implication of the findings of this study is that educators, parents and government officials need to cooperate in creating better and favourable environment for the teaching, learning and practice of Islamic studies in and outside the institutions of learning. Based on the findings of the study, it is recommended that tertiary educational institutions in Nigeria should re-orientate the degree being awarded graduates of Islamic studies to reflect the multi-disciplinary nature of the subject, that the subject needs to be taken more seriously by the government by making it core subject for all Muslim students up to Tertiary education level and that parent-teachers-school relationship be intensified to improve students' attitude towards the subject in schools.